1982
DOI: 10.1002/j.1460-2075.1982.tb01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific monoclonal antibodies in the assignment of the gene for human fibronectin to chromosome 2.

Abstract: Using three different species‐specific monoclonal antibodies we have studied, in human‐mouse and human‐hamster somatic cell hybrids, the correlation between the presence of different human chromosomes and the ability to release human fibronectin into the tissue culture medium. Presence of human fibronectin was determined by an affinity‐radioimmunoassay. In addition, tissue culture media of the different hybrids were separated on SDS‐polyacrylamide gels, the proteins were blotted onto a nitrocellulose sheet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…2 in hu man x mouse cell hybrids (Koch et al. 1982;Zardi et al, 1982;Prowse et al. 1985) and on the No.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2 in hu man x mouse cell hybrids (Koch et al. 1982;Zardi et al, 1982;Prowse et al. 1985) and on the No.…”
Section: Discussionmentioning
confidence: 96%
“…8 carries a gene that specifies FN attachment to the cell membrane. Zardi et al (1982) also mapped FN to the No. 2 by determining the soluble FN secreted by human x mouse hybrids with an immunoelectrophorelic assay and species-specific antisera as well as with an ELISA assay and monoclonal antibodies.…”
mentioning
confidence: 99%
“…These antibodies were derived from two in dependent hybrid clones as shown by the fact that they belong to two different Ig classes; however, competition binding experiments indicated that these antibodies are directed against the same or partially overlapping epi topes. Species-specific antibodies are useful reagents when it is important to unequivo cally establish the origin of fibronectin mole cules [33].…”
Section: Discussionmentioning
confidence: 99%
“…16132 Genova, Italy the primary transcript of a single gene 16-131 localized on chromosome two [14,15].…”
Section: Fibronectinsmentioning
confidence: 99%